Fine-tuning of two-dimensional metal–organic nanostructures via alkali–pyridyl coordination. Issue 5 (28th April 2020) - Zhou, Kun; Liang, Huifang; Wang, Miao; Xing, Shuaipeng; Ding, Honghe; Song, Yang; Wang, Yuxu; Xu, Qian; He, Jing-Hui; Zhu, Junfa; Zhao, Wei; Ma, Yu-qiang; et al.
Abstract : Fine-tuning of 2D metal–organic nanostructures is realized by alkali–pyridyl coordination. Abstract : Herein, we report a fine-tuning of the two-dimensional alkali–pyridyl coordination assemblies facilely realized by surface reaction between tetrapyridyl-porphyrin molecules and alkali halides on Ag(111) under a solventless ultrahigh vacuum condition. High-resolution scanning tunneling topography and X-ray photoelectron spectra reveal the formation of alkali–pyridyl coordination and the induced conformational tuning of the porphyrin macrocycle cores. Furthermore, employing other different alkali halide substitutes, we demonstrate a fine-tuning of the metal–organic nanostructures at the sub-Å scale. Postdeposition of Fe onto the as-formed precursor layer yields a two-dimensional bimetallic framework structure, manifesting a functionalization of the metal–organic interfaces.